Informace pro fuzzy mnoziny v diagnostice nemocí - Půlpán, Z (Acta medica (Hradec Kralove). Supplementum, 2000)
The mathematics offers the formal models in which variables and parameters can have the different interpretation. The application of formal model is then in the hands of experience and mostly also of knowledge, out of the mathematical way. Hence it followed that in the case, when the function of certain model is ensured by the software of computer, the everybody user to have know of a structure of mathematical models, their sense and possibilities. For example we have any object the role of fuzzy--mathematics in the one medical diagnostic situation. We shall attempt to show that the fundamental concepts of the theory of semantic information can be defined in a very straightforward way on the basis of the theory of fuzzy semantic information that has been recently developed by Zadeh and Shannon.
Keywords: Fuzzy Logic; expertní systémy; fuzzy logika; Expert Systems; diagnóza počítačová; Diagnosis, Computer-Assisted; Humans; lidé